Cosmic voids, spatial algorithms and data structures - Gómez-Vargas, Isidro; Medel-Esquivel, Ricardo; García-Salcedo, Ricardo (Journal of physics. Conference series, 2019)
Cosmic voids are regions with low density in the large scale structure of the universe. These cosmic structures are discovered from simulated or observational galaxy catalogs. In this work, we expose a slight overview of the importance of cosmic voids in cosmology and the type of algorithms used for its discovery in data sets. The octrees, hierarchical spatial data structures, are proposed as an available option to find cosmic voids in galaxy catalogs.